RAFTER STRUCTURE ANALYSIS USING WEB-TAPERED STEEL MEMBERS WITH THE FINITE ELEMENT METHOD - Astasya, Nita; Hamdi, Kamal (Fakultas Teknik Universitas Khairun, 2025)
AbstractBuilding design using steel materials that generally use prismatic cross-sections can be modified with a modified cross-section with the aim of cutting costs. This research was conducted with the aim of modifying an existing structure of the building, which are in the form of a steel construction with prismatic members, to replace it with a modified web-tapered steel members. Design analysis is conducted based on the results of modeling output on SAP2000 and numerical analysis based on SNI standards and applicable AISC’s Steel Design Guide books. This paper will show the stages of analysis, calculation, section capacity, and the cross-sectional size of the design results of the structure.